Revaluando el sionismo y la causa palestina: Intelectuales argentinos frente al conflicto árabe-israelí. Recepción y debates durante la Guerra de los Seis Días (1967) - Kahan, Emmanuel Nicolás (Anuario de Historia de América Latina, 2021)
One of the representations commonly held about the 1960’s is the enshrinement of the public intellectual as one of the period’s most prominent figures. The paths, programs and positions assumed by those personalities who encouraged the public debate, contemplating a stage with diverse alternatives to foster “liberation” (be it international, national or individual), was one of the period’s characteristic traits. At the national level, most studies enshrined a certain figure of the public intellectual, defined by the positions assumed with regards to a specific agenda focused on issues such as the redefinition of the relationship between Peronism and the left; and —in the aftermath of the Cuban Revolution— the option for guerrilla warfare as a valid alternative in the struggle for a more egalitarian society. However, many of the intellectuals who participated in those debates —as well as many who did not, or at least never received much academic recognition— also took positions on a broader universe of topics, which were particularly significant in that historical context. Such was the case, for example, of the Arab-Israeli conflict and the tensions arising around the Palestine cause and Zionism. This paper proposes to draw a map of those interventions, trying to evaluate the ways in which these debates on an extra-territorial conflict became a platform for conveying positions that were in fact stemming from the political and intellectual agenda at the national level.